2006
DOI: 10.1002/ajmg.a.31368
|View full text |Cite
|
Sign up to set email alerts
|

The new bone biology: Pathologic, molecular, and clinical correlates

Abstract: Bone and cartilage and their disorders are addressed under the following headings: functions of bone; normal and abnormal bone remodeling; osteopetrosis and osteoporosis; epithelial-mesenchymal interaction, condensation and differentiation; osteoblasts, markers of bone formation, osteoclasts, components of bone, and pathology of bone; chondroblasts, markers of cartilage formation, secondary cartilage, components of cartilage, and pathology of cartilage; intramembranous and endochondral bone formation; RUNX gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
204
0
26

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 287 publications
(234 citation statements)
references
References 394 publications
(510 reference statements)
4
204
0
26
Order By: Relevance
“…Furthermore, the dynamic responses of plasma concentration of NTproCNP, growth plate expansion and growth plate content of CNPs are positively related, underpinning the view that the hormone's production is intimately involved in linear growth. Previous studies indicate that over or under CNP activity, in contrast to some other essential growth factors in cartilage (Cohen 2006), have concordant effects on the skeletal phenotype without causing skeletal deformity (Kake et al 2009, Olney et al 2009). These observations are consistent with the findings in vitro showing that CNP acts positively at multiple sites (and at different phases) of chondrogenesis -the combined effects of which greatly augment the orderly expansion (Kake et al 2009) of the growth plate.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the dynamic responses of plasma concentration of NTproCNP, growth plate expansion and growth plate content of CNPs are positively related, underpinning the view that the hormone's production is intimately involved in linear growth. Previous studies indicate that over or under CNP activity, in contrast to some other essential growth factors in cartilage (Cohen 2006), have concordant effects on the skeletal phenotype without causing skeletal deformity (Kake et al 2009, Olney et al 2009). These observations are consistent with the findings in vitro showing that CNP acts positively at multiple sites (and at different phases) of chondrogenesis -the combined effects of which greatly augment the orderly expansion (Kake et al 2009) of the growth plate.…”
Section: Discussionmentioning
confidence: 99%
“…This may account in part for the abundance of osteoclast-like multinucleated giant cells usually seen in GCTOB because NFkB together with c-fos and RANKL regulate the differentiation of osteoclasts from preosteoclasts. 17,18 Interestingly, TP73L whose protein product is p63 was among the significantly upregulated genes identified for GCTOB even though none of the earlier gene expression profiling studies on GCTOB identified p63 as being highly expressed. 15,16,19 A closer examination of the TP73L expression in this series of tumors revealed that its expression was the highest in four of the six GCTOB whereas the other two GCTOB showed similar levels of TP73L expression as seen in ABC and FD.…”
Section: Gene Expression Profiling Studymentioning
confidence: 99%
“…Many of the overexpressed genes such as RUNX2, BMP2, SPARC, TNFRSF11B and ALPL are known to be important in the process of bone resorption and formation. 18 GSEA was performed to identify specific pathways that are upregulated in individual tumor types and the NFkB pathway showed relative upregulation in GCTOB although statistical significance was not reached (P ¼ 0.08). This may account in part for the abundance of osteoclast-like multinucleated giant cells usually seen in GCTOB because NFkB together with c-fos and RANKL regulate the differentiation of osteoclasts from preosteoclasts.…”
Section: Gene Expression Profiling Studymentioning
confidence: 99%
“…The osteoblasts lying on the bone surface become quiescent (resting phase) lining cells (Hill, 1998). With the completion of normal bone formation, approximately 70% of osteoblasts can be expected to undergo apoptosis, with the rest developing into osteocytes or more frequently, the bone-lining cells (Cohen, 2006). These bone-lining, osteoblast-like cells regulate the flow of mineral ions to the bone extracellular fluid, making up the blood-bone barrier, and can even re-differentiate to osteoblasts in time of need (Seeman, 2009).…”
Section: Par Stephen Mcmanusmentioning
confidence: 99%